Structure and Function of Centromeric and Pericentromeric Heterochromatin in Arabidopsis thaliana - Simon, Lauriane; Voisin, Maxime; Tatout, Christophe; Probst, Aline V. (Frontiers in Plant Science, 2015)
The centromere is a specific chromosomal region where the kinetochore assembles to ensure the faithful segregation of sister chromatids during mitosis and meiosis. Centromeres are defined by a local enrichment of the specific histone variant CenH3 mostly at repetitive satellite sequences. A larger pericentromeric region containing repetitive sequences and transposable elements surrounds the centromere that adopts a particular chromatin state characterized by specific histone variants and post-translational modifications and forms a transcriptionally repressive chromosomal environment. In the model organism Arabidopsis thaliana centromeric and pericentromeric domains form conspicuous heterochromatin clusters called chromocenters in interphase. Here we discuss, using Arabidopsis as example, recent insight into mechanisms involved in maintenance and establishment of centromeric and pericentromeric chromatin signatures as well as in chromocenter formation.